Haploinsufficiency for BRCA1 is associated with normal levels of DNA nucleotide excision repair in breast tissue and blood lymphocytes - Johnson Jennifer M; Rubinstein Wendy S; Latimer Jean J; Kanbour-Shakir Amal; Vogel Victor G; Grant Stephen G (BMC, 2005)
Abstract Background Screening mammography has had a positive impact on breast cancer mortality but cannot detect all breast tumors. In a small study, we confirmed that low power magnetic resonance imaging (MRI) could identify mammographically undetectable tumors by applying it to a high risk population. Tumors detected by this new technology could have unique etiologies and/or presentations, and may represent an increasing proportion of clinical practice as new screening methods are validated and applied. A very important aspect of this etiology is genomic instability, which is associated with the loss of activity of the breast cancer-predisposing genes BRCA1 and BRCA2. In sporadic breast cancer, however, there is evidence for the involvement of a different pathway of DNA repair, nucleotide excision repair (NER), which remediates lesions that cause a distortion of the DNA helix, including DNA cross-links. Case presentation We describe a breast cancer patient with a mammographically undetectable stage I tumor identified in our MRI screening study. She was originally considered to be at high risk due to the familial occurrence of breast and other types of cancer, and after diagnosis was confirmed as a carrier of a Q1200X mutation in the BRCA1 gene. In vitro analysis of her normal breast tissue showed no differences in growth rate or differentiation potential from disease-free controls. Analysis of cultured blood lymphocyte and breast epithelial cell samples with the unscheduled DNA synthesis (UDS) assay revealed no deficiency in NER. Conclusion As new breast cancer screening methods become available and cost effective, patients such as this one will constitute an increasing proportion of the incident population, so it is important to determine whether they differ from current patients in any clinically important ways. Despite her status as a BRCA1 mutation carrier, and her mammographically dense breast tissue, we did not find increased cell proliferation or deficient differentiation potential in breast epithelial cells from this patient which might have contributed to her cancer susceptibility. Although NER deficiency has been demonstrated repeatedly in blood samples from sporadic breast cancer patients, analysis of blood cultured lymphocytes and breast epithelial cells for this patient proves definitively that heterozygosity for inactivation of BRCA1 does not intrinsically confer this type of genetic instability. These data suggest that the mechanism of genomic instability driving the carcinogenic process may be fundamentally different in hereditary and sporadic breast cancer, resulting in different genotoxic susceptibilities, oncogene mutations, and a different molecular pathogenesis.